Alginate nanoparticles coated with chitosan-loaded PLGA microparticles for a delivery of hydrophilic drug - Ang, Jing Wen (2016)
Drug delivery is the transportation of pharmaceutical compounds in the body to attain its therapeutic effect in the patient. Traditional drug delivery systems often require continual drug administration, which can lead to fluctuation in the plasma levels and also stimulate toxic reactions. Thus, the purpose of this project is to develop a microcapsule system with drug-loaded nanoparticles encapsulated, to release drug in a controlled and sustained manner with different release profiles of the drug that can be altered by the selection of materials.